Hukum Dalam Tantangan Perlindungan Penyandang Disabilitas Terhadap Kekerasan Seksual - Iqbal, Muhamad; Indriani, Iin (Prodi Hukum S1 - Fakultas Hukum - Universitas Pamulang, 2024)
Gender-based violence is defined as any action that results in physical harm or emotional distress, including threats of harm with certain behaviors, coercion to engage in harmful behaviors, and various forms of freedom-limiting oppression.One of the most pervasive and harmful forms of HAM violation is sexual violence, which includes both overt acts of violence and those that are more covert in nature, such as those caused by cultural and societal biases against the victims. Research in the field of law is research that employs specific methodologies, frameworks, and philosophies in order to analyze a particular legal phenomenon. The key topics of this investigation are intellectual property rights and commercial secrecy. The primary laws used in this study are the Manufacturing Act of 1999. This study makes use of qualitative data analysis. To be conceited in the Ucapan Jurisprudence: Any action taken with the intention of causing another person to behave in a way that is inconsistent with their own personal values is known as ancaman or ancaman. Lack of Integrity in Concrete Work Product Expression (Memaksa and Memperkosa): To